The effect of articulate storyline 3-based interactive learning media on fourth-grade students’ interest in Learning Pancasila Education - Sandrianus Wolo Daki; Maxsel Koro; Treesly Adoe (ARKA INSTITUTE, 2026)
This study aims to determine the effect of using Articulate Storyline 3-based interactive learning media on increasing the learning interest of fourth-grade students in the Pancasila Education subject, specifically regarding the topic of Rights and Obligations, at SDK Don Bosko 4 in Kupang. This study employed a quantitative method using a pre-experimental design of the one-group pretest-posttest type. The sample consisted of 20 students selected using a saturation sampling technique. Data collection was conducted through a learning interest questionnaire using a Likert scale that had been tested for validity and reliability. Data were analyzed using normality tests, paired-sample t-tests, and effect size calculations. The results indicated a significant effect of using Articulate Storyline 3-based interactive learning media on students’ learning interest. This was evidenced by the paired-sample t-test yielding a significance value of 0.008 (p < 0.05). The average student learning interest score increased from 66.60 on the pretest to 76.10 on the posttest. Additionally, the effect size calculation yielded a Cohen’s d value of 0.97, which falls into the large category. Thus, Articulate Storyline 3-based interactive learning media has been proven effective in increasing students’ learning interest in the Pancasila Education subject in elementary school.